A preliminary investigation into the immune cell landscape of schistosome‐associated liver fibrosis in humans. Issue 8 (6th August 2021) - Zhang, Yu; Li, Junhui; Li, Hao; Zhou, Zhaoqin; Guo, Chen; Jiang, Jie; Ming, Yingzi
Abstract: Schistosomiasis is a widespread helminth disease that poses a heavy social and economic burden on people worldwide. Advanced schistosomiasis often develops into schistosome‐associated liver fibrosis, the pathogenesis of which remains unclear. This study aimed preliminarily to profile immune cells of schistosome‐associated liver fibrosis using single‐cell RNA sequencing. Three patient groups were enrolled, including an Schistosomiasis japonicum (SJ) group ( n = 1), a chronic liver failure (CLF) group ( n = 3) and a healthy control (HC) group ( n = 2), revealing 17 cell clusters out of 20 093 cells. From these limited datasets, it was observed that T cell(1), mononuclear phagocytes‐1 and dendritic cells (DCs) were higher in the SJ group. CAVIN2 + MP(2) was the predominant cell type in the MP subset of the SJ group (53%), and was higher than that in both the CLF (8%) and HC (1%) groups. Kupffer cell marker genes ( CD163, MARCO and TIMD4 ) were enriched in caveolae‐associated protein 2 ( CAVIN2 ) + MP(2), which was also an important source of TGFB1 . The KEGG pathways of CAVIN2 + MP(2) indicated that they were associated with lysosome, endocytosis, phagosome and antigen processing and presentation. The preliminary study showed that granzyme B ( GZMB ) + T cell(1) and ankyrin repeat domain‐containing protein 36B + T cell(3) were the most common T cells in the SJ group (50% and 32%, respectively). The KEGG pathways of GZMB + T cell(1) were mainly related to natural killer cell‐mediated cytotoxicity. The percentage of ring1 and YY1 binding protein ( RYBP ) + DC(1) was higher in the SJ group (57%) than in the CLF (16%) and HC (6%) groups. The KEGG pathway of RYBP + DC(1) was related to Fc gamma R‐mediated phagocytosis and antigen processing and presentation. Overall, CAVIN2 + Kupffer cells were the main source of TGFB1, consisting primarily of mononuclear phagocytes in the livers of the SJ group subjects and potentially playing an irreplaceable role in hepatic fibrosis of schistosomiasis. Abstract : The data in this study provide a reference map of the liver immune landscape of patients with schistosoma‐associated liver fibrosis.